PERANCANGAN DAN IMPLEMENTASI SISTEM PENDETEKSI KEBAKARAN DENGAN MENGGUNAKAN REALTIME DATABASE: Laksamana Rajendra Haidar Azani Fajri,Ngaseri ,Moh Muthohir - Azani Fajri, Laksamana Rajendra Haidar; Ngaseri; Muthohir, Moh (Jurnal Ilmiah Sistem Informasi, 2023)
Fires can occur unexpectedly, even if you are careful when using equipment that produces fire. However, there are still several sources that cause fires, such as electrical short circuits, gas stoves, burning rubbish, cigarette butts and candles when the lights go out. The aim of this research is to create a tool that can detect fire and temperature in a room and can overcome (minimize) the threat of fire disasters based on a microcontroller and C language. This research uses a Fire Sensor to detect fire, a DHT 11 Sensor to detect room temperature, NODEMCU as microcontroller controlling input and output, Buzzer as a system monitoring tool. The system will be assigned to turn on the extinguishing system that uses a FAN if there is a significant increase in temperature or if the system detects a fire. The output from the Flame Sensor which detects fire will be processed into a microcontroller which has been programmed using C language so that it will produce two states, namely low, namely when no fire is detected, and high when fire is detected. Likewise for the output from DHT11. This tool will give a warning to the buzzer if it detects a fire, and also detects changes in temperature and gives orders to spray the fan if there is a significant change in temperature